2003
DOI: 10.2746/042516403776148165
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant equine growth hormone administration: effects on synovial fluid biomarkers and cartilage metabolism in horses

Abstract: Summary Reasons for performing study: Recombinant equine growth hormone (reGH) has recently been evaluated for effects on body condition and wound healing. It has the potential to influence articular cartilage via stimulation of IGF‐1. Objectives: To investigate effects of administration on synovial joint metabolism. Methods: Six mature horses were given 20 μg/kg bwt reGH daily for 8 weeks by i.m. injection. Three control horses were injected with sterile water. Serum and synovial fluid samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Studies in animal models have shown that direct injection of IGF-I into the joint or administration of GH which results in an increase in the concentration of IGF-I in joint fluid are trophic for growth plate cartilage during normal development and for articular cartilage during the development of osteoarthritis (13, 3942). IGF-I synergizes with other growth factors such as EGF, TGFα and FGF to enhanced proteoglycan synthesis and cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models have shown that direct injection of IGF-I into the joint or administration of GH which results in an increase in the concentration of IGF-I in joint fluid are trophic for growth plate cartilage during normal development and for articular cartilage during the development of osteoarthritis (13, 3942). IGF-I synergizes with other growth factors such as EGF, TGFα and FGF to enhanced proteoglycan synthesis and cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…The most natural, effective and cost-efficient method to increase serum levels of IGF-I is through systemic administration of GH (Rosen 2000). Of noted interest to equine clinicians are studies which demonstrate the capacity of GH administration to reverse age-associated loss of bone marrow cells, improve recovery of skeletal muscle from hindlimb cast-immobilisation and to improve the healing capacity of cartilage (Dart et al 2003) and tendon (Rosen 2000). All of these beneficial effects of GH therapy may aid in the rehabilitation of individuals suffering musculoskeletal trauma as well as improve the quality of life for aged horses.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant equine growth hormone (reGH) was first marketed in Australia Ò ) in order to improve the positive nitrogen balance in horses over 15 years (Malinowski et al 1997). However, it is also suspected to be diverted from its original purpose to improve physical performance and wound healing (Dart et al 2003). In this context, the racing rules have strictly prohibited the use of recombinant equine growth hormone in France.…”
Section: Introductionmentioning
confidence: 99%